Mineralogy and geochemistry of oil shale in Azerbaijan: classification, palaeoweathering and maturity features - Aliyev, Adil A.; Abbasov, Orhan R.; Agayev, Agamehdi M. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Shamakhi-Gobustan and Absheron regions (Azerbaijan) are a part of the South Caspian Basin, which is a subsiding basin located between the colliding of Arabian and Eurasian plates. The intensive rate of sedimentation process creates a favorable condition for the formation of oil shale, hydrocarbon and as well as mud volcanoes in these regions. The purpose of the article. The study of oil shale in Azerbaijan has been mainly devoted to their geological and organic-geochemical characteristics, etc. However, the chemical classifications, provenience, palaeoweathering and maturity characteristics have not been studied. This study is the first attempt to investigate noted issues. The research methodology. 10 samples from the outcrops and eject of mud volcanoes were analyzed. The concentrations of major and trace elements and minerals were measured by “S8 TIGER Series 2 WDXRF”, “Agilent 7700 Series ICP-MS” mass spectrometers and XRD “MiniFlex 600”. The microscopes “Loupe Zoom Paralux XTL 745” and “MC-10” and a digital camera “OptixCam” were used to determine the age of the samples. The major and trace elements in the composition of samples were compared with average shale, NASC, PAAS and average black shale as well as oil shale from the Green River Formation of USA, Kukersit of Estonia, etc. studied in the published literature. A diagram and index were used for the classifications and determination of maturity of rocks. The palaeoweathering characteristic was determined based on CIA versus ICV and some other plots and ratios. Research results. The minerals found in oil shale were classified according to their classes. According to the used classification diagram, it was established that all studied samples correspond to shale. A superiority of clay minerals in the composition of oil shale compared to K-minerals, including K-feldspar was found. The estimates based on geochemistry and some ratios of elements confirm the instability of oxides and minerals, and immaturity of the samples. The values of the CIA, CIA versus ICV plot, etc. confirm moderate to high degree of weathering. The results confirm a conclusion that the original sediments were derived from mafic and intermediate source terrain. The scientific novelty. The scientific analysis presented in the paper is based on several substantial theoretical conclusions, which related to the factual material of research conducted by the co-authors. The mineralogy, classification features, stability characteristics of the major oxides and minerals as well as chemical maturity and palaeoweathering were studied based on the chemical composition of the samples. The practical significance. The results of the current study can be used for the further utilization of oil shale in Azerbaijan and the selection of promising areas in terms of mineral raw materials.